Changes in preschool children's OHRQoL after treatment of dental caries: responsiveness of the B‐ECOHIS. Issue 4 (15th September 2015) - Abanto, Jenny; Paiva, Saul Martins; Sheiham, Aubrey; Tsakos, Georgios; Mendes, Fausto Medeiros; Cordeschi, Thais; Vidigal, Evelyn Alvarez; Bönecker, Marcelo
Abstract : Background: Oral health‐related quality of life (OHRQoL) measures should be tested for responsiveness to change if they are to be used as outcomes in randomized clinical trials. Aim: To assess the responsiveness of the Brazilian ECOHIS (B‐ECOHIS) to dental treatment of dental caries. Methods: One hundred parents of 3‐ to 5‐year‐old children completed the B‐ECOHIS prior to their children's treatment and 7–14 days after completion of treatment. The post‐treatment questionnaire also included a global transition judgment that assessed parent's perceptions of change in their children's oral health following treatment. Change scores, longitudinal construct validity, standardized effect sizes (ES) and standardized response mean (SRM) were calculated. Results: Improvements in children's oral health after treatment were reflected in mean pre‐ and post‐treatment B‐ECOHIS scores. They declined considerably significantly from 17.4 to 1.6 ( P < 0.0001), as did the individual domain scores ( P < 0.0001). There were significant differences in the pre‐ and post‐treatment scores of children who reported little improvement ( P < 0.0001) as well as in those who reported large improvements ( P < 0.0001). The ES and SRM based on change scores mean for total scores and for categories of global transitions judgments were large. Conclusions: Dental treatment resulted in significant improvement of the preschool children's OHRQoL. The B‐ECOHIS is responsive.